Self-perceived social relationships are related to health risk behaviors and mental health in adolescents - Pereira da Silva, Danilo Rodrigues; Werneck, André de Oliveira [UNESP]; Agostinete, Ricardo Ribeiro [UNESP]; Bastos, Afrânio de Andrade; Fernandes, Rômulo Araújo [UNESP]; Vaz Ronque, Enio Ricardo; Cyrino, Edilson Serpeloni (FapUNIFESP (SciELO), 2021)
Although changes have been observed in social relationships in the recent years, especially among younger generations, little evidence is available concerning factors associated with adolescents’ perceived social relationships. In this study we investigated the association between self-perceived social relationships, health-related behaviors, biological maturation, and mental health in adolescents. This is a cross-sectional study conducted with 1,336 adolescents (605 boys and 731 girls) aged between 10 to 17 years from public schools. Self-perceived social relationships (family, friends, and teachers), feelings of stress and sadness, academic performance, tobacco smoking, alcohol and fat consumption, physical activity, and screen time were evaluated by a questionnaire. Biological maturation was assessed by the peak height velocity. We observed that worse perceived social relationships were associated with tobacco smoking (family and teachers), alcohol drinking (teachers), higher consumption of fat (teachers), greater feelings of stress (family and teachers) and sadness (family and friends), and poor academic achievement (friends and teachers).
A percepção dos relacionamentos sociais está relacionada à comportamentos de risco associados à saúde e à saúde mental em adolescents
Keywords: Academic performance; Healthy lifestyle; Mental disorders; Social support